Lab-on-a-chip : miniaturized systems for (bio)chemical analysis and synthesis - Oosterbroek, R. Edwin; Berg, A. van den (Albert) (Elsevier, 2003)
In the past ten years there has been a rapid growth of the research and application area known as Lab-on-a-Chip. After an initial focus on electrokinetic separation techniques on chip, the scope of the field has widened to include topics like microfluidics, DNA analysis, cell analysis, microreactors and mass spectrometer interfacing. As well as the analytical chemistry community, synthetic chemists, chemical engineers, biochemists and biomedical engineers are now also becoming more and more interested in using new micro- and nanotechnological techniques. This first Lab-on-a-Chip book contains a broad collection of papers on microtechnology, microfluidics, analytical methods and applications. All contributions are written by leading researchers in their respective fields, and provide new scientists with an overview of the field, to make him/her aware of the enormous opportunities offered by modern technology. The work presented in this book will definitely stimulate readers to new ideas and concepts, and lead to further innovations in this area. - Provides a quick introduction into the different aspects of this field - Describes technology that has already revolutionized the world of chemical and biochemical analysis and synthesis - All contributions are written by leading researchers in their respective fields.